UPAYA MEMBANGUN DESTINATION BRANDING WISATA HALAL DI LABUHAN MANGROVE JUNG KONENG KABUPATEN BANGKALAN: Elisa Helmalia Helda, Anik Sunariyah - Helmalia Helda, Elisa (Qawwam : The Leader's Writing, 2022)
Tourism is a major sector driving the economy in the world including Indonesia, currently halal tourism has become a topic of conversation, many tours have a halal concept and are not well known due to the lack of destination branding efforts in these tours. Destination branding is very influential on regional tourism development. The purpose of this study was to find out what efforts and steps were taken in building halal tourism destination branding by managers and the community at the Jung Koneng Labuhan Mangrove Tourism, Bangkalan. The type of research used is descriptive qualitative which is considered very appropriate for reviewing the application of rules in detail, while the data source is obtained from scientific literature searches which have included various field reviews related to interview materials and documentation. Various kinds of interesting facts related to halal tourism, which in fact this context is still difficult to apply in Indonesia, especially in Bangkalan district, this is because there are many systems and regulations that still do not accommodate halal tourism. The results obtained from this study say that Labuhan Mangrove has carried out several stages of destination branding such as the brand launch and introduction stage, building image, personality and character, only need to carry out other branding stages and need to get wider support so that the Halal tourism concept of Labuhan Mangrove develops.